Medals of Spanish Freemasonry: The Democratic Six Years (1868-1874). Documentary and Iconographic Analysis - Cuadrado Merchán, Manuel (2019)
After the fall of Isabella II in 1868, Spain witnessed a new era of freedom hitherto unknown. This meant that Spanish Freemasonry could operate publicly within the law. During the Six Year Democracy, Freemasonry experienced the emergence of obedience’s and lodges. During the following turbulent years, many Spanish lodges joined Portugal’s Freemasonry looking for masonic regularity not found in the new Spanish obedience. Some medals related to this period have been preserved and we have analyzed them and their iconography as numismatic objects in order to shed some light on this artistic manifestation of Spanish Freemasonry.